2011
DOI: 10.1016/j.mri.2011.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of image registration between MRI and light microscopy in the ex vivo brain

Abstract: A multi-step procedure was developed to register magnetic resonance imaging (MRI) and histological data from the same sample in the light microscopy image space, with the ultimate goal of allowing quantitative comparisons of the two datasets. The fixed brain of an owl monkey was used to develop and test the procedure. In addition to the MRI and histological data, photographic images of the brain tissue block acquired during sectioning were assembled into a blockface volume to provide an intermediate step for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 21 publications
1
69
0
Order By: Relevance
“…Moreover, the histology sections may not be cut exactly perpendicular to the axis of spinal cord tracts, which in turn may also cause biased estimations. 3D OGSE measurements and histology analyses may overcome these effects, but an accurate and sophisticated imaging co-registration procedure covering in vivo applications should be used (Choe et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the histology sections may not be cut exactly perpendicular to the axis of spinal cord tracts, which in turn may also cause biased estimations. 3D OGSE measurements and histology analyses may overcome these effects, but an accurate and sophisticated imaging co-registration procedure covering in vivo applications should be used (Choe et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Eighteen cortical regions of interest (ROIs) in the frontal and parietal lobes were manually labeled by an experienced neuroanatomist on the digitized Nissl-stained slides (labelling was performed using ITK-SNAP, Version 2.4.0). The labels in micrograph space were transformed to the frozen blockface space, and subsequently to the native ex vivo high resolution diffusion weighted space by a multi-step registration procedure described in (Choe et al 2011), a process shown to result in registration errors of approximately one MRI voxel (300um in that study). Thus, for each of 3 monkeys, 18 cortical labels exist in ex vivo diffusion space.…”
Section: Methodsmentioning
confidence: 99%
“…Performing voxel-based registration allows for spatially local comparison of MRI and histology, and the scale of this analysis is dependent on the achievable registration accuracy. Many previous studies in MRI and histology registration (see Table 3 2004; Meyer et al, 2006;Lebenberg et al, 2010;Schormann et al, 1995;Yelnik et al, 2007;Osechinskiy and Kruggel, 2011;Bardinet et al, 2002), and furthermore many previous studies included evaluation on only one dataset (Malandain et al, 2004;Choe et al, 2011;Meyer et al, 2006;Schormann et al, 1995;Kim et al, 2000;Yelnik et al, 2007;Osechinskiy and Kruggel, 2011;Bardinet et al, 2002;Lazebnik et al, 2003). Of the studies that did report accuracy on more than one dataset, TRE ranged from sub-millimeter (Ceritoglu et al, 2010;Jacobs et al, 1999;Yang et al, 2012) to 3-5 mm (Liu et al, 2012;Singh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, there have also been many studies specifically dealing with in-vivo brain MRI to post-mortem histology. The majority of these studies focused on primates (Dauguet et al, 2007;Malandain et al, 2004;Breen et al, 2005;Ceritoglu et al, 2010;Choe et al, 2011) or rodents (Jacobs et al, 1999;Humm et al, 2003;Meyer et al, 2006;Lebenberg et al, 2010;Yang et al, 2012;Liu et al, 2012). The few studies that registered human brain MRIto histology were performed on wholebrain (Schormann et al, 1995;Kim et al, 2000;Singh et al, 2008), or single hemisphere (Yelnik et al, 2007;Osechinskiy and Kruggel, 2011) post-mortem serially sectioned data (Amunts et al, 2013) created a 3D model of single subject's brain using post-mortem histological sections reconstructed at 20 m isotropic resolution and registered it to a T1 average atlas created from 24 subjects.…”
Section: Introductionmentioning
confidence: 99%